The Relationship Of The Weight Of Newborn Babies And The Incident Of Perineal Rupture In Primipara Mothers At Rb Mutiara Bunda - IMAS, NOVIANTI RIZKI AMALIA; Chairiyah, Royani (Journal of Nursing and Midwifery Sciences, 2024)
The first cause of bleeding is uterine atony and the second cause is tearing of the birth canal. One of the birth canal tears is a perineal tear. Perineal rupture is an injury to the perineum that occurs due to certain reasons without any tearing or deliberate action. The aim of the research was to determine the relationship between newborn baby weight and the incidence of perineal rupture in primiparous mothers. This research method is analytical research with a cross sectional approach. The population was 86 primiparous mothers who experienced perineal rupture or did not experience perineal rupture. The results of the study showed that the weight of newborn babies in primiparous mothers ranged between 2500-4000 grams (61.6%), 64 mothers experienced perineal rupture (74.4%), primiparous mothers whose babies weighed > 4000 grams experienced perineal rupture. as many as 14 people (100%). The conclusion is that there is a relationship between the weight of newborn babies and the incidence of perineal rupture in primiparous mothers at RB Mutiara Bunda.